2017
DOI: 10.1039/c7ra07610j
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of microbial dynamics and phosphorus removal for a two side-stream wastewater treatment processes

Abstract: A side-stream process with anoxic/aerobic tanks was designed as a denitrifying enhanced biological phosphorus removal process for wastewater treatment as compared to a modified side-stream process using contact/stabilization tanks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Acinetobacter-0.2-2.4% in R1, 0.3-2.4% in R2, and 0.0-2.6% in R3-persistent but usually low in abundance in AGS reactors [46], were also found. Environmental conditions control the abundance of each bacterial species [47].…”
Section: Distribution Of the Microbial Profilementioning
confidence: 99%
“…Acinetobacter-0.2-2.4% in R1, 0.3-2.4% in R2, and 0.0-2.6% in R3-persistent but usually low in abundance in AGS reactors [46], were also found. Environmental conditions control the abundance of each bacterial species [47].…”
Section: Distribution Of the Microbial Profilementioning
confidence: 99%
“…Dechloromonas phosphorivorans abundances ranging from 0.1 to 1.9% in EBPR facilities and observed up to 1% relative abundance in non-EBPR facilities. Prior to that study and the proposal of the Dechloromonas PAO taxonomic classification, unclassified Dechloromonas were enriched in a variety of lab-scale and full-scale EBPR bioreactors. , To our knowledge, no other full-scale studies have identified Dechloromonas, specifically Ca . Dechloromonas phosphorivorans, as a key PAO in S2EBPR configurations.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of GAOs might interfere with the accumulation of poly-P by PAOs. 11 The PHA compounds contained PHB and PHV, and their values increased with the release proceeding. The increased PHA content accelerated the disintegration and the following cell lysis of anaerobic sludge.…”
Section: Intracellular Phosphorus Contentsmentioning
confidence: 95%
“…In addition, anaerobic sludge is the pool of microorganisms for P release, which relies on a group of bacteria, i.e., phosphorus accumulating organisms (PAOs). 11 PAOs could store carbon sources as intracellular polymeric (poly-b-hydroxyalkanoate, PHA) and release ortho-P from the microbial cells using the energy of the degradation of glycogen and polyphosphate (poly-P). [12][13][14] PAOs are identied as mesophiles or even psychrophiles.…”
Section: Introductionmentioning
confidence: 99%